Type of obstetric anesthesia administered and complications in women with preeclampsia in low- and middle-income countries: A systematic review - Soha Sobhy; Kuhan Dharmarajah; David Arroyo-Manzano; Ramesan Navanatnarajah; James Noblet; Javier Zamora; Shakila Thangaratinam (Taylor & Francis Group, 2017)
Background: Delivery is often expedited with cesarean section, necessitating anesthesia, to prevent complications in women with preeclampsia. Anesthesia-associated risks in these women from low- and middle-income countries (LMICs) are not known. Methods: We searched major databases (until February 2017) for studies on general vs. regional anesthesia in women with preeclampsia. We summarized the association between outcomes and type of anesthesia using a random effects model and reported as odds ratio (OR) with 95% confidence intervals (95% CIs). Findings: We included 14 studies (10,411 pregnancies). General anesthesia was associated with an increase in the odds of maternal death sevenfold (OR 7.70, 95% CI 1.9 to 31.0, I2 = 58%) than regional anesthesia. The odds of pulmonary edema (OR 5.16, 95% CI 2.5 to 10.4, I2 = 0%), maternal intensive care unit admissions (OR 16.25, 95% CI 9.0 to 29.5, I2 = 65%), and perinatal death (OR 3.01, 95% CI 1.4 to 6.5, I2 = 56%) were increased with general vs. regional anesthesia. Conclusion: General anesthesia is associated with increased complications in women with preeclampsia undergoing cesarean section in LMIC.